On finite A-groups with complementable nonmetacyclic subgroups - Baryshovets, P. P. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study groupsG satisfying the following conditions: (i)G is a finite solvable group with non-Abelian commutant and Abelian Sylow subgroups; (ii) all nonmetacyclic subgroups ofG are complementable. We give a description of the structure of such groups with nonmetacyclic second commutant.